China: Saviour or Challenger of the Dollar Hegemony?. Issue 6 (4th November 2013) - Hung, Ho‐fung
ABSTRACT: Since the collapse of the Bretton Woods monetary order in 1971, the US dollar has successfully maintained its global hegemony despite the US's declining share in the global economy, thanks largely to the US's political‐military supremacy. The recent rise of China poses a serious dilemma to the US. On the one hand, China's export‐oriented development has provided the US with low‐cost manufactured imports and cheap credit. On the other hand, the US's expanding current account deficit, largely attributable to China, has precipitated a crisis of confidence over the dollar's long‐term viability. This dilemma explains the US's vacillation in its currency conflict with China over the last decade. China has also been caught in a dilemma. While keeping its currency cheap could help sustain its export competitiveness, it would deepen China's dependence on the US market and Treasury bonds as an outlet for its expanding current account surplus. On the other hand, while a RMB revaluation would facilitate China's long overdue economic rebalancing and reduce its dependence on the US, the resulting unravelling of the long‐entrenched export‐oriented growth could generate large‐scale economic dislocation. No matter how this currency conflict is settled, its final resolution will determine the future of the dollar's global hegemony.